Potential of Fermented Rice Bran as a Functional Food Ingredient to Prevent Colon Cancer - Nurul Dwi Fitriani (Perum BULOG, 2023)
Rice bran is a by-product of rice processing rich in bioactive compounds. These bioactive compounds include phenolic, flavonoid, steroidal components, and anthocyanins. The activity of bioactive compounds in rice bran can be enhanced by a biotechnological process, namely fermentation. The fermentation process in rice bran increases the phenolic component due to the breakdown of complex phenolic compounds with several enzymes produced by microorganisms. Fermented bran containing abundant bioactive components has the potential as a functional food to prevent colon cancer. In vitro and in vivo studies showed that fermented bran prevent the development of colon cancer better than non-fermented bran. Prevention of colon cancer based on in vivo and in vitro studies can be through increasing the expression of apoptotic genes, decreasing proliferation marker genes, and decreasing pro-inflammatory cytokines. The process of preventing colon cancer with bioactive components can be through induction of apoptosis and inhibition of cancer cell proliferation, protection of cells against free radicals, deregulation of the Wnt/β-catenin signaling pathway, and enhancement of the immune response.